Media Pembelajaran Sebagai Alat Bantu Dalam Keberhasilan Proses Belajar Mengajar - Abdul Kosim; Rizal Nurwidhia; Arbitra Achmad Fahrezi Saputra; Choirul Anwari; Firdatul Aini; Rada Fitriana; Dila Abdatillah Ad-Afah7 (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This learning media aims to develop and improve elementary school students' learning. This media is a development media that uses meta analysis methods. One of the problems in education is the minimum media facilities and infrastructure, so teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media in the classroom. An interesting learning media that can overcome students' boredom in learning activities is game-based learning activities, such as the application of the snakes and ladders game media. Children at the elementary level have a tendency to play. A fun and relaxed situation will help children to increase their interest in learning. The development of learning media in the form of the snakes and ladders game has the impact of providing discourse about alternative teaching media for elementary level. It is hoped that the use of this learning media can improve the quality of teaching and learning activities at the basic level.